IT/IS Strategic Planning pada Sektor Edukasi Studi Kasus Universitas Bakrie (Jurnal Teknologi Terpadu, 2017)
The using of Information Technology  in higher education institutions have become the success key of teaching & learning  process, research and academic administration. Universitas bakrie has been established for ten years. Over time the deployment of IS/IT at the Universitas Bakrie have been progressing. But in 3 years before, it appears that the plan is not entirely referring to vision, mission and process business of Universitas Bakrie. Therefore in this research aims to discussing about the IS/IT strategic planning at Unversitas Bakrie. The design process is based to a model IS/IT strategic planning (Ward & Peppard,2002) where the steps consisting of analysis of the external and internal environment  Universitas Bakrie and analysis of the external and internal environment IS/IT Universitas Bakrie. After the analysis is done, IS/IT strategic planning, IS/IT management planning and the implementation of the design IS/IT planning in 3 years. Finally the result of this research is expected to give a description of IS/IT strategic planning to be used as reference in IS/IT planning annual in Universitas Bakrie. Key words        : higher education, strategic plan, IS/IT strategic Plan